Strain Tuning via Larger Cation and Anion Codoping for Efficient and Stable Antimony‐Based Solar Cells. Issue 1 (23rd November 2020) - Nie, Riming; Lee, Kyoung Su; Hu, Manman; Seok, Sang Il
Abstract: Strain induced by lattice distortion is one of the key factors that affect the photovoltaic performance via increasing defect densities. The unsatisfied power conversion efficiencies (PCEs) of solar cells based on antimony chalcogenides (Sb‐Chs) are owing to their photoexcited carriers being self‐trapped by the distortion of Sb2 S3 lattice. However, strain behavior in Sb‐Chs‐based solar cells has not been investigated. Here, strain tuning in Sb‐Chs is demonstrated by simultaneously replacing Sb and S with larger Bi and I ions, respectively. Bi/I codoped Sb2 S3 cells are fabricated using poly[2, 6‐(4, 4‐bis(2‐ethylhexyl)‐4H‐cyclopenta[2, 1‐b;3, 4‐b']dithiophene)‐alt‐4, 7‐(2, 1, 3‐enzothiadiazole)] as the hole‐transporting layer. Codoping reduced the bandgap and rendered a bigger tension strain (1.76 × 10 −4 ) to a relatively smaller compression strain (−1.29 × 10 −4 ). The 2.5 mol% BiI3 doped Sb2 S3 cell presented lower trap state energy level than the Sb2 S3 cell; moreover, this doping amount effectively passivated the trap states. This codoping shows a similar trend even in the low bandgap Sb2 (Sx Se1‐x )3 cell, resulting in 7.05% PCE under the standard illumination conditions (100 mW cm −2 ), which is one of the top efficiencies in solution processing Sb2 (Sx Se1‐x )3 solar cells. Furthermore, the doped cells present higher humidity, thermal and photo stability. This study provides a new strategy for stable Pb‐free solar cells. Abstract : Strain tuning in Sb‐Chs was demonstrated by simultaneously replacing Sb and S with larger Bi and I ions, respectively. This strategy has been applied in Sb2 (S x Se1– x )3 solar cells, and the champion cell exhibits a PCE of 7.05% under the standard illumination conditions (100 mW cm −2 ), which is one of the top efficiencies in solution processing Sb2 (S x Se1– x )3 solar cells.